Designing an Optimal Model Regarding Early Warning System of Bankruptcy of Banks in Iran Application of Grounded Theory and Econometric Models - Hojjatollah Keshavarz Haddadha; Hamidreza Alipour; Sina Kheradyar (Environmental Energy and Economic Research)
In financial and banking system and macroeconomic conditions develop a comprehensive document for the banking early warning system (BEWS) for monetary and banking policy makers is important. The main objective of the present study is to design and estimate the native model regarding the early warning system of bankruptcy threshold of banks in Iran. Based on the strategy of Grounded Theory, the native model designed. Also, according to the optimization criteria, the optimal model was chosen. The methodology is mixed. In the qualitative part, information is obtained through in-depth interviews by guiding generalities and in a semi-structured way. In the quantitative part, the research hypotheses were tested using data from the panel data for a ten-year period (2011-2020). The results obtained in the qualitative part have shown that capital adequacy, bank competitiveness index and bank stability have been identified as indicators of bankruptcy threshold of banks (dependent variables). Nine variables were identified as explanatory variables. According to the criteria of the optimal model, the third model is the optimal model from the point of view of all the criteria. Moreover, the residual sum of squares of the third model is lower than the other two models. The Durbin-Watson value is much closer to 2, so it is a healthier model and it can be claimed that there is no correlation error in the error term. Finally, in the third model, the value of F statistic is much higher than other models.